2004
DOI: 10.1542/peds.114.2.497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of the Human Immunodeficiency Virus-1—Exposed Infant

Abstract: ABSTRACT. In developed countries, care and treatment are available for pregnant women and infants that can decrease the rate of perinatal human immunodeficiency virus type 1 (HIV-1) infection to 2% or less. The pediatrician has a key role in prevention of mother-tochild transmission of HIV-1 by identifying HIV-exposed infants whose mothers' HIV infection was not diagnosed before delivery, prescribing antiretroviral prophylaxis for these infants to decrease the risk of acquiring HIV-1 infection, and promoting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 60 publications
0
10
0
7
Order By: Relevance
“…Therefore, this sample seems to be representative of the wide variety of HIV disease in pediatrics [15,16,18]. Even though standard therapy for pediatric patients is based on the combination of one protease inhibitor or one non-nucleoside reverse transcriptase inhibitor plus two nucleoside analog reverse transcriptase inhibitors (NRTI) [16,20], most of our patients were receiving a regimen based on the combination of two PIs plus two NRTIs, because most of them came from a cohort being evaluated for comparison of two different antiretroviral regimens [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this sample seems to be representative of the wide variety of HIV disease in pediatrics [15,16,18]. Even though standard therapy for pediatric patients is based on the combination of one protease inhibitor or one non-nucleoside reverse transcriptase inhibitor plus two nucleoside analog reverse transcriptase inhibitors (NRTI) [16,20], most of our patients were receiving a regimen based on the combination of two PIs plus two NRTIs, because most of them came from a cohort being evaluated for comparison of two different antiretroviral regimens [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that children with perinatally acquired HIV-1 infections start to have symptoms earlier than adult patients [18,43,44], and usually have higher VLs [15,18,20,43]. The VL at the initiation of HAART and at the time of audiologic evaluation was higher in patients with HL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 -30 In many resource-rich countries, programs for PMTCT incorporate 6 weeks' neonatal ARV prophylaxis as standard practice. 4,5,8 Discussion continues as to whether in non-breastfeeding populations abbreviated-neonatal ARV regimens can yield optimal results. As yet the long-term outcome of in utero and neonatal ARV exposure remains to be fully defined, however, given the known potential for adverse events, 9,12,[31][32][33] it is reasonable to limit exposure where possible, provided the very real benefit of preventing HIV transmission is not compromised.…”
Section: Discussionmentioning
confidence: 99%
“…3 US guidelines recommend 6-week neonatal ARV prophylaxis for exposed infants. 4,5 This derives from the pivotal ACTG 076 study, 6 but the absolute need for a 6-week treatment duration is not evidencebased. Animal model data support 4 weeks duration for prophylaxis after a definite inoculation.…”
mentioning
confidence: 99%